A biopsychosocial approach assessing pain indicators among Black men - Baker, Tamara A.; Morales, Knashawn H.; Brooks, Amber K.; Clark, Jaylyn F.; Wakita, Anna; Whitt-Glover, Melicia C.; Yu, Yelia Z.; Murray, Marcus; Hooker, Steven P. (Frontiers in Pain Research, 2023)
The lack of empirical evidence documenting the pain experience of Black men may be the result of social messaging that men are to project strength and avoid any expression of emotion or vulnerability. This avoidant behavior however, often comes too late when illnesses/symptoms are more aggressive and/or diagnosed at a later stage. This highlights two key issues – the willingness to acknowledge pain and wanting to seek medical attention when experiencing pain. To better understand the pain experience in diverse raced and gendered groups, this secondary data analysis aimed to determine the influence identified physical, psychosocial, and behavioral health indicators have in reporting pain among Black men. Data were taken from a baseline sample of 321 Black men, > 40 years old, who participated in the randomized, controlled Active & Healthy Brotherhood (AHB) project. Statistical models were calculated to determine which indicators (somatization, depression, anxiety, demographics, medical illnesses) were associated with pain reports. Results showed that 22% of the men reported pain for more than 30 days, with more than half of the sample being married (54%), employed (53%), and earning an income above the federal poverty level (76%). Multivariate analyses showed that those reporting pain were more likely to be unemployed, earn less income, and reported more medical conditions and somatization tendencies (OR=3.28, 95% CI (1.33, 8.06) compared to those who did not report pain. Findings from this study indicate that efforts are needed to identify the unique pain experiences of Black men, while recognizing its impact on their identities as a man, a person of color, and someone living with pain. This allows for more comprehensive assessments, treatment plans, and prevention approaches that may have beneficial impacts throughout the life course.